Assessment of service quality and restaurant attributes on customer satisfaction among restaurant users in Ibadan metropolis (2017)
Service quality is fundamental components which produce higher level of customer satisfaction, which in turn leads to increased repurchase intention. A significant amount of literature has emerged, which has increased our understanding of the difficulties associated with delivering service quality, however need for service managers with the tools they need to put quality control into action is important. In this study, perception of service quality and restaurant attributes and its impact on customer satisfaction were assessed among traditional restaurant users in Ibadan metropolis. A multistage sampling procedure was used to sample 126 respondents from four (4) Local Government Areas in Ibadan metropolis. Questionnaire was administered to collect data on respondents' socio-economic characteristics, perceived service quality of restaurants and satisfaction on restaurants. Data were analyses using descriptive (frequencies, percentages, means and ranks) and inferential (Chi-square, Pearson's Product Moment Correlation and Linear regression) sat p=0,05. Mean age of respondents was 29.11 years with majority being single (69.8%), male (58.7%), Yoruba (81.7%), students (33.3%), with mean income of N91186.51 and majority (94.4%) having tertiary education as their highest form of education. Perceived service quality was high. Overall satisfaction on restaurants was high 58.7%. Respondents ethnicity (X2-7.905), occupation (X2=12.750), age (r=0.295), income (r=0.226) were significantly related to customer satisfaction in restaurants. Also, perceived service quality (r=0.624) was significantly related to customer satisfaction in restaurants.